(3^x-5).7=83
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 8697-(37:35+2(13-3)
=8697-(32+2.13-2.3)
=8697-(9+26-6)
=8697-29
=8668
b) 2010-2000:(486-2(72-6))
=2010-2000:(486-(2.49-2.6))
=2010-2000:(486-(98-12)
=2010-2000:400
=2010-5
=2005
c)718:716+22.33.32.5-22.7+83
=(718:716)+(22.33.32)-(22.7)+83
=49+972-28+83
=1076
nhớ tích nha bạn ^-^
\(5\dfrac{3}{4}:3+2\dfrac{1}{4}\times\dfrac{1}{3}-\dfrac{1}{8}=\left(5\dfrac{3}{4}+2\dfrac{1}{4}\right)\times\dfrac{1}{3}-\dfrac{1}{8}\\ =8\times\dfrac{1}{3}-\dfrac{1}{8}=\dfrac{8}{3}-\dfrac{1}{8}=\dfrac{61}{24}\\ ----\\ \dfrac{3}{5}:\dfrac{5}{6}:\dfrac{6}{7}:\dfrac{7}{8}+\dfrac{2}{5}+\dfrac{23}{35}\\ =\dfrac{3}{5}\times\dfrac{6}{5}\times\dfrac{7}{6}\times\dfrac{8}{7}+\dfrac{2}{5}+\dfrac{23}{35}=\dfrac{18}{25}\times\dfrac{4}{3}+\dfrac{2}{5}+\dfrac{23}{35}=\dfrac{353}{175}\)
43 x 166 + 14 x 83
= 43 x ( 83 x 2 ) + 14 x 83
= (43 x 2) x 83 + 14 x 83
= 86 x 83 + 14 x 83
= ( 86 + 14 ) x 83
= 100 x 83
= 8300
43 x 166 + 14 x 83
= 43 x ( 83 x 2 ) + 14 x 83
= ( 43 x 2 ) x 83 + 14 x 83
= 86 x 83 + 14 x 83
= 83 x ( 86 + 14 )
= 83 x 100
= 8300
\(\frac{7}{2}\)- \(\frac{3}{2}\): x = \(\frac{5}{4}\)
\(\frac{3}{2}\): x = \(\frac{7}{2}-\frac{5}{4}\)
\(\frac{3}{2}\): x = \(\frac{14}{4}-\frac{5}{4}\)
\(\frac{3}{2}\): x = \(\frac{9}{4}\)
x = \(\frac{3}{2}:\frac{9}{4}\)
x = \(\frac{3}{2}x\frac{9}{4}\)
x = \(\frac{27}{8}\)
1: -5>-10
=>x-5>x-10
2: -4>-8
=>x-4>x-8
3: 2>-6
=>x+2>x-6
4: -3<7
=>x-3<x+7
5: 5<8
=>x+5<x+8
6: 10>7
=>x+10>x+7
Bài 1:
a: \(x=\dfrac{2}{3}:\dfrac{3}{5}=\dfrac{2}{3}\cdot\dfrac{5}{3}=\dfrac{10}{9}\)
b: \(x=\dfrac{17}{8}:\dfrac{7}{17}=\dfrac{17}{8}\cdot\dfrac{17}{7}=\dfrac{289}{56}\)
c: \(x=-\dfrac{3}{4}:\dfrac{7}{12}=\dfrac{-3}{4}\cdot\dfrac{12}{7}=\dfrac{-63}{28}=-\dfrac{9}{4}\)
d: \(\Leftrightarrow x\cdot\dfrac{1}{6}=\dfrac{3}{8}-\dfrac{1}{4}=\dfrac{1}{4}\)
hay \(x=\dfrac{1}{4}:\dfrac{1}{6}=\dfrac{3}{2}\)
e: \(\Leftrightarrow\dfrac{1}{2}:x=-4-\dfrac{1}{3}=-\dfrac{17}{3}\)
hay \(x=-\dfrac{1}{2}:\dfrac{17}{3}=\dfrac{-3}{34}\)
b: \(\left[\left(6+\dfrac{3}{5}-3-\dfrac{3}{14}\right)\cdot\dfrac{2}{5}\right]:\left(21-1.25\right)=x:\left(5+\dfrac{5}{6}\right)\)
\(\Leftrightarrow x:\dfrac{35}{6}=\dfrac{237}{175}:\dfrac{79}{4}\)
\(\Leftrightarrow x:\dfrac{35}{6}=\dfrac{12}{175}\)
\(\Leftrightarrow x=\dfrac{2}{5}\)
\(\Leftrightarrow3^x-5=\dfrac{83}{7}\)
\(\Leftrightarrow3^x=\dfrac{118}{7}\)